Ideological eclecticism of political parties – the ideological profile in practice - Filipczak-Białkowska, Anita (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter presents the course and results of the project aimed at diagnosing Polish political discourse. The research sought answers to the question: "Does the Polish party system show ideological differentiation?". The obtained results confirmed the formulated research hypothesis, according to which the parties operating in the Polish political system during the so-called The Fourth Republic of Poland was diverse in terms of the ideology represented. Analytical work was carried out on the basis of an extensive material base consisting of texts of parliamentary debates. The project used the method of ideological discourse analysis based on the assumptions of communicative grammar and taking into account the common research area of linguistics and political science.